Prognostic significance of hypoxic and metabolic gene profiling in hepatocellular carcinoma. Issue 1 (12th May 2021) - Milosa, Fabiola; Critelli, Rosina Maria; Lasagni, Simone; Pivetti, Alessandra; Di Marco, Lorenza; Romagnoli, Dante; Carulli, Lucia; Dituri, Francesco; Mancarella, Serena; Giannelli, Gianluigi; Martinez‐Chantar, Maria‐Luz; Fabris, Luca; et al.
Abstract: Background & Aims: Hepatocellular carcinoma (HCC) is characterized by high clinical and biological heterogeneity, depending on the extremely variable combinations of pathways, linked with immune mechanisms, neo‐angiogenesis, ECM remodeling, metabolism and/or hypoxia. We recently identified a 5‐genes neo‐angiogenic transcriptomic signature (TS), able to discriminate between "aggressive" HCCs (TS‐positive) from "bland" HCCs (TS negative), the former having extremely poor survival. The aim of this study was to compare gene expression of our HCC cohort with gene expression of well‐characterized, published signatures, which have been related with several different functions potentially relevant in carcinogenesis (ie immune control, hypoxia, metabolism, vascular invasion). We also aimed to ascertain the prognostic power for survival. Methods: The gene expression profile of a cohort of 78 HCC patients prospectively identified were analysed according to a series of published gene expression signatures related with hypoxia, metabolism and immunity and related with the ability of the signature to predict survival. Results: Only few genes described in the various immune‐signatures analyzed were differentially expressed and were related with reduced survival in our prospective cohort, especially in TS‐positive HCCs. Genes composing hypoxic, metabolic and vascular invasion signatures were instead much more deregulated both in aggressive or bland HCCs. For most of them, the level of expression related with reduced survival. This suggests their possible value as biomarker of tumor aggressiveness. Conclusion: Altogether, our data demonstrate that in HCC, and especially in aggressive TS‐positive HCC, signaling pathways related with hypoxic and metabolic/glycolytic signatures are more relevant in determining a poorer outcome of HCC than immune‐related pathways.